Community Dispositions to Undergraduates’ Social Media Addiction and Poor Study Habits as Correlates of Undergraduates’ Low Achievement in Ogun State, Nigeria - Olubela, Afolabi; Iyunade, Olufunmilayo (Journal of Pedagogy and Education Science, 2025)
Social media addiction and other variables, such as poor study habits, have been attributed to students’ low academic achievement. Students who engage more on social media will basically exhibit poor study habits and performance. This study examined the community dispositions to undergraduates’ social media addiction and poor study habits as correlates of undergraduates’ low achievement in Ogun State. This study adopted a descriptive survey research design. A sample of 100 community members was randomly selected from Ijebu-Ode, Sagamu, and Abeokuta. These include landlords/ladies, transporters, market men and women, and eatery workers. Data were collected using a validated instrument titled: students' social media addiction and study habit questionnaire (SSMA-SH, r=0.76). The three research questions were analysed using Descriptive frequency tables and means cores.  There was also a significant influence of students’ social media addiction and poor study habits on low academic achievement. The study recommended that institutions should educate students about the negative influence of excessive social media and integrate academic activities, such as assignments or discussions, on social media platforms to foster a habit of using these platforms for educational purposes among students.